Maqāṣidī's Approach to Qiwāmah and Nafaqah: Finding Gender Justice in Modern Islamic Family Law - Awalul, Abdurrohman; Mawariza, Putri; Ardian Syah , Jefry; Nuranisah, Nuranisah (Yapilin Press, 2025)
This study reviews the concepts of qiwāmah (husband's leadership) and nafāqah (maintenance obligation) in Islamic family law through the maqāṣid al-sharī'ah approach as an effort to find gender justice in the context of the modern Muslim family. Historically, both concepts have often been interpreted hierarchically and patriarchally, which has an impact on the inequality of roles and rights between men and women. This research aims to reinterpret the meaning of qiwāmah and nafāqah based on the principles of maqāṣid al-sharī'ah such as ḥifẓ al-nafs, ḥifẓ al-nasl, and ḥifẓ al-'ird, so as to give birth to a more substantive and contextual understanding. Using a qualitative-descriptive method based on literature studies, this study examines classical and contemporary sources, including the thought of al-Ghazālī, Ibn 'Āshūr, and Jasser Auda. The results of the study show that the maqāṣidī approach is able to shift the meaning of qiwāmah into a collective moral responsibility and nafāqah as a participatory economic responsibility. These findings confirm that gender justice in Islamic family law is not a form of liberalization, but rather the actualization of the sharia's benefit-oriented goals (maṣlaḥah). This research makes a conceptual contribution to the development of contemporary Islamic law methodologies and offers a basis for reforming family law norms in Indonesia to be more responsive to the values of equality and justice